Pembentukan Sikap Oleh Perokok Remaja Melalui Peringatan Bahaya Merokok Pada Kemasan Rokok - Negoro, Sherly Hindra (Interaksi: Jurnal Ilmu Komunikasi, 2016)
Abstract:Indonesian Government announced to the cigarette industrial to showed pictorical warning on cigarette packs. The goal was to reduce amount of Indonesian smoker. This research was conducted at Yogyakarta among of smoker adolescents (200 samples). Hypothesis test was formed by using software PLS (Partial Least Square) and t-test with software SPSS. Their behavior was on action stage of behavior steps was to reduce smoking frequently.. Based on research we got conclusion that there are significant influence between knowledge and risk perception with attitude and behavior as intervening variable. Although, cognitive dissonance theory couldn’t enough explain with altogether.Keywords: knowledge, risk perception, behavior, attitude